Međimurje Church Singing. Echoes in the “Katolički list” (Catholic Newspaper) - Tomić, Draženko; Legac, Vladimir (Acta humanitarica academiae Saulensis, 2024)
Međimurje is a region in the northwest of the Republic of Croatia. Among its many peculiarities, it is characterised by specific folk lyrical solo vocal female singing, the so-called Međimurska popevka (Folk song from Međimurje). In 2013, that traditional Međimurje song was declared an intangible cultural good of the Republic of Croatia. In 2018, it was put on the list of elements on UNESCO’s Representative List of the Intangible Cultural Heritage of Humanity. This article presents the results of the authors’ research into the writings of the weekly Katolički list (Catholic Newspaper) (Zagreb, 1849–1945) about Međimurje singing. It can be seen from the weekly that the people of Međimurje attracted attention with their singing at all church ceremonies and on other occasions. However, with the Caecilian reform of church singing (1870–1920), which was more intense in Croatia from 1907 onwards, Međimurje singing began to be valued differently by some individuals (mainly priests). Echoes of these musical turmoils are also found in the weekly Katolički list. Although the entries of this weekly must be thoroughly supplemented with a description of the socio-political circumstances of the time, including Međimurje singing, and especially with the description of the nature of the Caecilian movement, the patriotic importance and traditional value of that folk singing in northwest Croatia can be strongly glimpsed in all the recorded texts.